Peso ecológico y diversidad en un bosque de colina baja de la comunidad campesina Anguilla, distrito de Alto Nanay, Loreto – Perú. 2024 - Huansi Oroche, Cesar Augusto Lenin (2025)
A study was conducted in a lowland forest in the rural community of Anguila, with the aim of determining its ecological weight and diversity. The floristic composition reports 592 trees, 21 species, 19 genera and 11 families. The Myristicaceae family reports 228 trees (38.5%) and Fabaceae 137 trees (23.1%), both families grouping more than 50% of the total trees in the lowland forest. Virola calophylla (56.3%), Carapa guianensis (24.1%), Otoba parvifolia (21.6%), Hymenaea oblongifolia (19.5%), Virola albidiflora (18.8%) and Aniba panurensis (16.4%) are the species with the greatest ecological weight. In the present study, the values indicate that the lowland forest presents a medium diversity. Promote forest inventories in diverse areas with sufficient detail to ensure results with the minimum margin of sampling error. Implement enrichment with the commercial species Virola calophylla due to its high importance index, with the goal of increasing the economic benefits of lowland forests. In reforestation plans, it is recommended to pay special attention to species classified as vulnerable, according to the results of the importance index.